ChemInform Abstract: Phase‐Transfer Catalysts in the O‐Alkylation of 2‐Hydroxynaphthoquinones. Issue 3 (22nd January 2013) - Lu, Xiao; Altharawi, Ali; Hansen, Emily N.; Long, Timothy E.
Abstract A mild procedure for the selective alkylation of the substrates at the 2‐hydroxy group is developed using a mixture of two phase‐transfer catalysts.